"It is not the same": relationships and dementia. Issue 7 (3rd July 2019) - Benbow, Susan Mary; Tsaroucha, Anna; Sharman, Victoria
ABSTRACT: People living with dementia may live in relationship with partners, family members, and significant others. Dementia has been shown to impact on such relationships but relationships also impact on the dementia condition. Thirteen people took part in the study: all were caring for a person living with dementia and two were themselves living with dementia. Semi-structured interviews were conducted with participants focusing on changes in close relationships, including changes in intimate (sexual) relationships where appropriate. Interviews were audiotaped, transcribed, and analyzed using thematic analysis. Four main themes were identified: changes in couple relationships; changes in non-partner relationships; talking about oneself in relationship; and talking about people with dementia in relationship. In conclusion, participants' lived experiences highlight the need for ongoing relational support and an education-based counseling program that could potentially address many of participants' highlighted needs.